Terapi Tawa pada Lansia - Naylil Mawadda Rohma; Rika Maya Sari; Sri Andayani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aimed to find out the summary of laughter therapy in the elderly. The method of reviewing systematic research on several works of literature (systematic review). Review method with PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis). The results showed that laughter therapy alone or a combination of other interventions (progressive muscle relaxation, Nurse-Led Intervention, Peer Support Group, giving honey monkeys) and a variety of hypertension exercises with laughter therapy could improve psychological and physical problems. The duration of each therapy session and the duration of treatment can be adjusted according to the ability of the elderly and elderly issues that can be solved within a minimum period of 3 weeks and a maximum of 8 weeks with a duration of 10 - 60 minutes and sessions per week adjusted (minimum 1x and maximum 3x in 1 week). Conclusion: Laughter therapy alone or in combination with other therapies can help improve the physical and psychological problems and mental health of the elderly. Nurses can provide laughter therapy as therapeutic care for the elderly with physical and psychological issues. Keywords: Elderly, Laughter Therapy